Karaman İlinde Yaşayan Boşanmış Kadınların Karar Verme Düzeylerinin İncelenmesi - Aydın, Elif (Fırat University, 2017)
Bu projenin amacı, Karaman ilinde yaşayan boşanmış kadınların, karar verme düzeylerinin belirlenerek, katılımcılara uygulanacak ölçekten elde edilen verilere göre; karar verme düzeyleri yüksek değerlere ulaşan kadınları tespit edebilmektir.Yapılan bu nitel çalışmada, araştırma grubunu, Karaman Aile ve Sosyal Politikalar İl Müdürlüğüne kayıtlı 10 boşanmış kadın oluşturmaktadır. Araştırmada, demografik bilgileri içeren soruların yanı sıra, Melbourne Karar Verme Ölçeği baz alınarak bazı sorular örneklem grubunu oluşturan boşanmış kadınlara sözel olarak yöneltilmiştir. Yapılan çalışmalardan elde edilen bu verilerin yanı sıra, araştırmamız neticesinde Karaman Aile ve Sosyal Politikalar İl Müdürlüğüne kayıtlı 10 boşanmış kadın ile yapılan görüşme sonrası elde edilen veriler doğrultusunda; katılımcıların eğitim durumlarının ilkokul ve ortaokul ile sınırlanmış olması, çocuklarına bakma yükümlülüğünden dolayı çoğunluğunun çalışamıyor olması ve çoğunun gelir sevilerinin düşük ve oturdukları evin kira olması gibi olumsuz etkenlere rağmen karar verme düzeylerinin yüksek olduğu tespit edilmiştir.

This study was done with the aim of the determination of the female reaching high levels of decision-making, after their life is examined psycho-social after their divorce, by determining the level of decisionmaking, of divorced female living in Karaman province, according to the results obtained from scales applied to participants. In this qualitative study, the research group consists of 10 divorced female registered with Karaman Family and Social Policy Provincial Directorate. Some questions of the mentioned scales were orally addressed to divorced female who constituted the sample group by being based on the Melbourne Decision Making Questionnaire as well as demographic information questions. In addition to these data obtained from the studies done, in line with the data obtained after the interview with 10 divorced female registered with Karaman Family and Social Policies Provincial Directorate, as a result of our research; while the level of decision making were found to be high as the educational status of the participants was limited to primary and secondary schools, the majority were unable to work because of their obligation to look after their children, and the majority of the income were low and the house rents were low, the level of state.
The Investigation Of The Divorced Women’s Making Decision Levels In Karaman Province